Trafficking in women and girls for the sex trade: the case of Greece - Emke-Poulopoulos, Ira (The Greek Review of Social Research, 2003)
Trafficking in women and children for the commercial sex industry and pornography exists in all societies. Greece is an important destination and to a lesser degree transit country. After presenting estimates and statistics on legal and undocumented status, nationality, age, educational and family status, this paper analyses the causes of trafficking in the countries of origin and destination as well as the role of the traffickers. Trafficking is examined as a) a violation of fundamental human rights of the victims and as a lucrative business of the criminal traffickers. The yearly profits were estimated at 1130 million euros in the year 2000 and b)a crime commited by the traffickers and supported by corruption of the public officials, especially police with pparticipation of the clients and the Mas Media. Policy on trafficking and forced prostitution is also presented.